Time-Varying Distributions and Dynamic Hedging with Foreign Currency Futures - Kroner, Kenneth F.; Sultan, Jahangir (Journal of Financial and Quantitative Analysis, 1993)
Kenneth F. Kroner, Jahangir Sultan, Time-Varying Distributions and Dynamic Hedging with Foreign Currency Futures, The Journal of Financial and Quantitative Analysis, Vol. 28, No. 4 (Dec., 1993), pp. 535-551